Implementation of Post-Training Evaluation (Case Study of Motorcycle Automotive Technique Training at Erlangga Blitar Course and Training Institute) - Lestari, Yuniarti Puji; Supriyono, Supriyono; Ahmad, Ahmad (Universitas Negeri Malang, 2024)
Becoming an automotive technician requires a deep understanding of the workings of the engine and the function of each part of a motorcycle. However, not all technicians have the opportunity to take part in Light Vehicle Engineering (TKR) training. One of the institutions that implements TKR training is the Erlangga Blitar Course and Training Institute (LKP), which has a program that is very relevant to the needs of students. However, evaluation is still needed in its implementation. Therefore, this study was conducted to identify the post-motorcycle automotive engineering training evaluation process at LKP Erlangga Blitar, identify the Standard Operating Procedure (SOP) for post-motorcycle automotive engineering training evaluation at LKP Erlangga Blitar, and analyze the use of post-training evaluation for the development of training programs at LKP Erlangga Blitar motorcycle automotive engineering training. This study uses a qualitative research method, with a case study research type. The research location is at LKP Erlangga Blitar. The data sources for this study consist of two (2) sources, namely primary data sources and secondary data sources. The primary data sources are the managers of LKP Erlangga Blitar and DUDI (Business World and Industry World). Meanwhile, secondary data sources are LKP Erlangga Blitar's social media and LKP Erlangga Blitar's profile. The data collection techniques used by the researcher are interviews, observations, and documentation studies. Data analysis was carried out since entering the field, while in the field, and after finishing in the field. During entering the field, the data analysis used by the researcher to analyze the interviewee's answers refers to the Miles & Huberman model analysis, where this data analysis consists of data reduction, data presentation, and verification. The validity test uses internal validation, external validity, reliability, and objectivity. The results of the study showed that the implementation of the post-training evaluation of motorcycle automotive engineering at LKP Erlangga Blitar began during the PKL report exam. After the PKL report exam session was completed, a question and answer session was continued. If the learners have been recruited for work, then the data is recorded in the tracer study. When the learners have been declared to have passed, the LKP Erlangga Blitar organizers asked for alumni testimonial videos and DUDI testimonials. The results of the post-training evaluation of Motorcycle Automotive Engineering at LKP Erlangga Blitar were used to develop the Motorcycle Automotive Engineering curriculum. In general, the implementation of post-training evaluation at the Automotive Motorcycle Engineering Training LKP Erlangga Blitar has become the institution's capital of excellence in building public trust, so that its graduates are absorbed in DUDI relatively quickly based on the skills they have, and helping partnerships with other institutions. The implication of this study is that the evaluation model that the institution already has can be used by other institutions based on partnerships with LKP, so that its graduates are absorbed in DUDI. Keywords: Post Training Evaluation, Course and Training Institution, Non-Formal Education